Plus minus Hedonism Lifestyle through Individual Counseling Services between Reality Approaches and Rational Emotive Therapy for Students of SMA Negeri 8 Medan - Nuraini Nuraini; Mahyarita Br Kaban; Maria Br Sembiring (Budapest International Research and Critics University, 2020)
This study aims to determine the effectiveness of the hedonistic lifestyle through individual counseling services between the reality approach and rational emotive therapy for students at SMA Negeri 8 Medan.The type of research used is descriptive qualitative. The subjects in this study were 8 students of SMA Negeri 8 Medan who have a high hedonistic lifestyle. Data collection methods used are observation, interviews, and scale. The results showed that the provision of Reality counseling services can have an effect on increasing students' self-concept. While the application of individual counseling approach to rational emotive behavior therapy to overcome learning difficulties in students. By modifying irrational thoughts into rational ones, more rational emotional and behavioral consequences will be formed. It can be concluded that there are pluses and minuses to the hedonistic lifestyle in students that can affect students' self-concepts.